2017
DOI: 10.1155/2017/8439259
|View full text |Cite
|
Sign up to set email alerts
|

Experiment of Carbonate Dissolution: Implication for High Quality Carbonate Reservoir Formation in Deep and Ultradeep Basins

Abstract: As the most frontiers in petroleum geology, the study of dissolution-based rock formation in deep carbonate reservoirs provides insight into pore development mechanism of petroleum reservoir space, while predicting reservoir distribution in deep-ultradeep layers. In this study, we conducted dissolution-precipitation experiments simulating surface to deep burial environments (open and semiopen systems). The effects of temperature, pressure, and dissolved ions on carbonate dissolution-precipitation were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Therefore, the faults are right-lateral left stepover obliquely distributed, and compressional uplifts are mainly developed in the overlapping section of faults. While, at the T 7 4 interface, the S-1 fault zone is under the background of tension torsion tectonic stress, the faults are left-lateral left stepover obliquely distributed as the consequence. In the faults overlapping section, pull-apart and drop-offs are mainly developed.…”
Section: At the Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the faults are right-lateral left stepover obliquely distributed, and compressional uplifts are mainly developed in the overlapping section of faults. While, at the T 7 4 interface, the S-1 fault zone is under the background of tension torsion tectonic stress, the faults are left-lateral left stepover obliquely distributed as the consequence. In the faults overlapping section, pull-apart and drop-offs are mainly developed.…”
Section: At the Tmentioning
confidence: 99%
“…At the early stage of the evolution of the S-5 strike-slip fault zone, the structural characteristics of a single strike-slip fault match to the Riedel shear model. In episode in the middle Caledonian period, a right-lateral left stepover strike-slip fault zone was developed on the T 7 4 interface, indicating that it was affected by NE direction compressive stress at the stage. The segmentation deformation characteristics of the S-5 strike-slip fault zone are caused by the local stress differences near the fault and the superposition of multi-stage faults.…”
Section: The S-5 Strike-slip Fault Zonementioning
confidence: 99%
See 1 more Smart Citation
“…Due to the increasing di culty of exploration and development of conventional oil and gas reservoirs worldwide, unconventional reservoirs have attracted increasing attention (Zou et al, 2014;He et al, 2017). The Tarim Basin, which is situated in the Xinjiang Uygur Autonomous Region of the People's Republic of China, is host to the T-Sh oil eld.…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the main gas fields in Changqing gas area. As for the Sinian gas reservoir in the Anyue gas field, Sichuan Basin, it is a monolithic weathering-crust carbonate rock gas reservoir with the oldest payzone, the most complex gas reservoir characteristics, and largest GIIP in China [9,10]. Currently, it is reported that GIIP of this gas reservoir amounts to trillions of cubic meters, and the gas field is building its production capacity.…”
Section: Introductionmentioning
confidence: 99%